CD157 Confers Host Resistance to Mycobacterium tuberculosis via TLR2-CD157-PKCzeta-Induced Reactive Oxygen Species Production - Qianting Yang (American Society for Microbiology, 2019)
ABSTRACT Recruitment of monocytes to the infection site is critical for host resistance against Mycobacterium tuberculosis. CD157 has a crucial role in neutrophil and monocyte transendothelial migration and adhesion, but its role in tuberculosis (TB) is unclear. Here, we show that both mRNA and protein levels of Cd157 are significantly increased during M. tuberculosis infection. Deficiency of Cd157 impaired host response to M. tuberculosis infection by increasing bacterial burden and inflammation in the lung in the murine TB model. In vitro experiments show that the bactericidal ability was compromised in Cd157 knockout (KO) macrophages, which was due to impaired M. tuberculosis-induced reactive oxygen species (ROS) production. We further reveal that CD157 interacts with TLR2 and PKCzeta and facilitates M. tuberculosis-induced ROS production in Cd157 KO macrophages, which resulted in enhanced M. tuberculosis killing. For the clinic aspect, we observe that the expression of CD157 decreases after effective anti-TB chemotherapy. CD157 is specifically increased in pleural fluid in tuberculous pleurisy patients compared to pneumonia and lung cancer patients. Interestingly, the levels of soluble CD157 (sCD157) correlate with human peripheral monocyte-derived macrophage bactericidal activity. Exogenous application of sCD157 could compensate for macrophage bactericidal ability and restore ROS production. In conclusion, we have identified a novel protective immune function of CD157 during M. tuberculosis infection via TLR2-dependent ROS production. Application of sCD157 might be an effective strategy for host-directed therapy against TB in those with insufficient CD157 production. IMPORTANCE Tuberculosis, a chronic bacterial disease caused by Mycobacterium tuberculosis, remains a major global health problem. CD157, a dual-function receptor and β-NAD+-metabolizing ectoenzyme, promotes cell polarization, regulates chemotaxis induced through the high-affinity fMLP receptor, and controls transendothelial migration. The role of CD157 in TB pathogenesis remains unknown. In this study, we find that both mRNA and protein levels of CD157 are significantly increased in TB. Deficiency of CD157 impaired host defense against M. tuberculosis infection both in vivo and in vitro, which is mediated by an interaction among CD157, TLR2, and PKCzeta. This interaction facilitates M. tuberculosis-induced macrophagic ROS production, which enhances macrophage bactericidal activity. Interestingly, the sCD157 level in plasma is reversibly associated with MDM M. tuberculosis killing activity. By uncovering the role of CD157 in pathogenesis of TB for the first time, our work demonstrated that application of soluble CD157 might be an effective strategy for host-directed therapy against TB.